Gravity anomalies, subsidence history and the tectonic evolution of the Malay and Penyu Basins (offshore Peninsular Malaysia) - Madon, M; Watts, A (1998)
The tectonic subsidence and gravity anomalies in the Malay and Penyu Basins, offshore Peninsular Malaysia, were analysed to determine the isostatic compensation mechanism in order to investigate their origin. These continental extensional basins contain up to 14 km of sediment fill which implies that the crust had been thinned significantly during basin development. Our results suggest, however, that the tectonic subsidence in the basins cannot be explained simply by crustal thinning and Airy isostatic compensation. The Malay and Penyu Basins are characterized by broad negative free-air gravity anomalies of between -20 and -30 mGal. To determine the cause of the anomaly, we modelled four gravity profiles across the basins using a method that combines two-dimensional flexural backstripping and gravity modelling techniques. We assumed a model of uniform lithospheric stretching and Airy isostasy in the analysis of tectonic subsidence. Our study shows that the basins are probably underlain by relatively thinned crust, indicating that some form of crustal stretching was involved. To explain the observed gravity anomalies, however, the Moho depth that we calculated based on the free-air gravity data is about 25% deeper than the Moho predicted by assuming Airy isostasy (Backstrip Moho). This suggests that the Airy model overestimates the compensation and that the basins are probably undercompensated isostatically. In other words, there is an extra amount of tectonic subsidence that is not compensated by crustal thinning, which has resulted in the discrepancy between the gravity-derived Moho and the Backstrip Moho. We attribute this uncompensated or anomalous tectonic subsidence to thin-skinned crustal extension that did not involve the mantle lithosphere. The Malay and Penyu Basins are interpreted therefore as basins that formed by a combination of whole-lithosphere stretching and thin-skinned crustal extension.